Hyperandrogenemia is Common in Asymptomatic Women and is Associated with Increased Metabolic Risk. Issue 1 (14th November 2019) - Torchen, Laura C.; Tsai, Joy N.; Jasti, Prathima; Macaya, Rodrigo; Sisk, Ryan; Dapas, Matthew L.; Hayes, M. Geoffrey; Urbanek, Margrit; Dunaif, Andrea
Abstract : Objective: Women with metabolic syndrome (MetS) have higher endogenous testosterone (T) levels than unaffected women. This study investigated whether hyperandrogenemia (HA) was a marker for increased cardiometabolic risk in reproductively normal premenopausal women. Methods: Reproductive hormones and metabolic parameters were assessed in 198 women with regular menses and no clinical hyperandrogenism (eumenorrheic [EM]). Hyperandrogenic EM women were compared with 110 women with NIH criteria polycystic ovary syndrome. Results: Twenty‐two percent of EM women had HA. Levels of non–sex hormone–binding globulin (SHBG)‐bound T were elevated in 68% of women, total T levels were elevated in 43% of women, and dehydroepiandrosterone sulfate levels were elevated in 30% of women. The prevalence of HA increased with BMI category ( P  = 0.01): 12% for BMI < 25 kg/m 2, 22% for BMI of 25 to 30 kg/m 2, and 31% for BMI ≥ 30 kg/m 2 . MetS (adjusted odds ratio 2.9; 95% CI: 1.2‐6.9) and dysglycemia risks (adjusted odds ratio 2.7; 95% CI: 1.2‐5.8) were increased in hyperandrogenic EM women compared with normoandrogenic EM women, with adjustment for BMI. SHBG levels were independently associated with these metabolic end points ( P  < 0.001), whereas androgen levels were not. A cluster analysis confirmed that there was a discrete subset of EM women with HA and metabolic abnormalities. Conclusions: HA is common in EM women and is associated with increased risks for MetS and dysglycemia. However, low SHBG levels rather than elevated androgen levels may be the primary predictor of this relationship with metabolic dysfunction.